2018
DOI: 10.1038/pr.2017.288
|View full text |Cite
|
Sign up to set email alerts
|

Placental lipid processing in response to a maternal high-fat diet and diabetes in rats

Abstract: BACKGROUNDDiabetes and obesity during pregnancy impact the health of both mothers and developing babies. Prevention focuses on glycemic control, but increasing evidence implicates a role for lipids. Using a rat model, we showed that a maternal high-fat (HF) diet, increased perinatal morbidity and mortality, but lipid processing across the maternal-placental-fetal triad remained unstudied. We hypothesized that HF diet would disrupt placental lipid processing to exaggerate fuel-mediated consequences of diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Dams that received streptozotocin but did not manifest a fasting blood glucose level ≥ 200 mg/dl were excluded from the study. While in our model all pregnant dams developed physiologic hyperlipidemia of pregnancy, diabetes increased serum triglycerides ∼2 fold, diet ∼3 fold, and the combination ∼5 fold higher than controls leading to corresponding hyperinsulinemia in offspring (30,(32)(33)(34). Thus, our model of late gestation diabetes plus HF diet translates to poorly controlled gestational diabetes or Type 2 diabetes in the developing offspring with exposure to glucolipotoxicity and fetal hyperinsulinemia.…”
Section: Animal Model Characteristicsmentioning
confidence: 86%
See 1 more Smart Citation
“…Dams that received streptozotocin but did not manifest a fasting blood glucose level ≥ 200 mg/dl were excluded from the study. While in our model all pregnant dams developed physiologic hyperlipidemia of pregnancy, diabetes increased serum triglycerides ∼2 fold, diet ∼3 fold, and the combination ∼5 fold higher than controls leading to corresponding hyperinsulinemia in offspring (30,(32)(33)(34). Thus, our model of late gestation diabetes plus HF diet translates to poorly controlled gestational diabetes or Type 2 diabetes in the developing offspring with exposure to glucolipotoxicity and fetal hyperinsulinemia.…”
Section: Animal Model Characteristicsmentioning
confidence: 86%
“…We previously demonstrated that combination exposed offspring (P1) are exposed to high levels of circulating maternal glucose and lipids which incite insulin and C-peptide overproduction in the offspring (30)(31)(32)(33)(34). This triad of maternal hyperglycemia and hyperlipidemia and fetal hyperinsulinemia causes insulin resistance with attendant downregulation of growth hormone receptors and less PI3K/AKT activation to drive a glycolysis-togluconeogenesis switch (33,(41)(42)(43).…”
Section: Downregulated Fgfr2/pi3k/akt Activation Underlies Metabolic mentioning
confidence: 99%
“…Oil Red O staining was performed on placenta cryosections, as described previously (Louwagie et al . ). Placenta samples including the labyrinth zone were excised, fixed with paraformaldehyde and embedded in OCT (Thermo 6502; Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 97%
“…Unfortunately, even when maternal hyperglycemia is well-controlled during pregnancy, the risk of heart disease in IDM persists [12,13,15,50]; this implicates additional targetable triggers including lipids. We previously used a rat model to show that a maternal HF diet compounded the effects of late-gestation diabetes by exposing the offspring not only to hyperglycemia, but also to hyperlipidemia which increased fetal insulin production, placental lipotoxicity, cardiac dysfunction, and perinatal mortality [26,51]. The present study used cardiac-speci c transcriptomic pro ling to identify potential underlying mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…We previously demonstrated that combination exposed offspring (P1) are exposed to high levels of circulating maternal glucose and lipids which incite insulin and C-peptide overproduction in the offspring [26][27][28][29]37]. This triad of maternal hyperglycemia and hyperlipidemia and fetal hyperinsulinemia causes insulin resistance with attendant downregulation of growth hormone receptors and less PI3K/AKT activation to drive a glycolysis-to-gluconeogenesis switch [29,[38][39][40].…”
Section: Downregulated Fgfr2/pi3k/akt Activation Underlies Metabolic mentioning
confidence: 99%